Essays on the roles of remittances and oil prices in an oil importing developing economy - Abubakar, Muhammad (2024)
This thesis investigates the effects of oil price fluctuations on oil-importing economies that heavily rely on remittances originating from oil-producing countries, using Pakistan as a case study. Pakistan is one of the largest exporters of labour (both skilled and unskilled), especially to the Gulf region, and is the recipient of substantial remittance inflows, which are notably high compared to foreign direct investment. The economic implications of oil prices and remittances have been extensively studied separately. However, despite the crucial link between the two, few studies capture both elements within the same model.